Does CPAP mitigate cardiovascular responses to submaximal effort in subjects with obstructive sleep apnea? A cross-sectional study (Research, Society and Development, 2021)
Objective: To compare functional exercise capacity (FEC) and cardiovascular responses to submaximal exercise in individuals with obstructive sleep apnea (OSA) with and without treatment with continuous positive airway pressure (CPAP). Methods: 73 individuals diagnosed with moderate or severe OSA were divided into 2 groups: CPAP group (good adherence ≥ 4 hours / night, n = 36) and nCPAP group (did not use the device, n = 37) and were submitted to the six-minute step test (6MST). Results: There was no difference between groups in the FEC (nCPAP 132.95 ± 27.12 steps vs CPAP 125.11 ± 26.15 steps; p = 0.213). The pressure response immediately after exercise (final - rest) was higher in the nCPAP group for both systolic blood pressure (SBP) (57.56 ± 19.91mmHg vs 28.88 ± 15.07mmHg; p = 0.000) and blood pressure diastolic (DBP) (14.05 ± 8.64 vs 1.38 ± 7.23; p = 0.000). The percentage of variation in recovery (recovery - initial) was lower in the CPAP group, both for PAS (24.2 ± 12.04% vs 4.6 ± 7.31%; p = 0.000) and for PAD (10.66 % ± 9.41% vs 0.43% ± 6.88%; p = 0.000). There was no difference in the percentage of HR variation (nCPAP 18.6 ± 15.34% vs. CPAP 15.08 ± 10.59%; p = 0.260). Conclusions: The results suggest an attenuated pressure response to submaximal effort and a faster recovery of SBP and DBP in individuals with OSA treated with CPAP compared to untreated ones.